Spleen-preserving surgical treatment of splenic artery aneurysm secondary to chronic pancreatitis and primary biliary cholangitis - Tanasković Slobodan (Serbian Medical Society, 2021)
Introduction. Splenic artery aneurysm (SAA) represents the third cause of abdominal aneurysms, just after abdominal aorta and iliac arteries aneurysms, with overall prevalence of 1%. Pancreatitis has been linked with pseudoaneurysm formation of SA due to destruction of arterial wall by pancreatic enzymes, however true SAA associated with pancreatitis has not been described yet. We are presenting the first case of true SAA in a patient with chronic pancreatitis and primary biliary cholangitis successfully treated by surgical excision, direct arterial reconstruction and spleen preservation. Case outline. A 74-year-old male patient was admitted for multidetector computed tomography angiography due to suspected SAA and renal artery aneurysm (RAA). He was previously treated for chronic pancreatitis and primary biliary cholangitis. Upon admission, computed tomography arteriography showed SAA 32 mm in diameter and RAA 12 mm with SAA being in direct contact with superior margin of the pancreas. Surgical treatment of SAA was indicated while RAA was treated conservatively. Intraoperatively, SAA adherent to the superior margin of pancreas was noted, followed by complete exclusion of the aneurysm and end-to-end splenic artery anastomosis. Histopathology showed atherosclerotic degeneration of arterial wall with all three layers presenting as true aneurysm. Two years after the surgery, control computed tomography angiography showed regular postoperative findings without further progression of RAA. Conclusion. This is the first case to describe a true SAA aneurysm originated on the field of previous episodes of chronic pancreatitis and primary biliary cholangitis. Surgical treatment including aneurysm resection and direct arterial reconstruction with spleen preservation showed satisfactory results.